Design, Microwave‐Assisted and Conventional Synthesis of New Hybrid Compounds Derived From 1‐(4‐Fluorophenyl)piperazine and Screening for Their Biological Activities. Issue 7 (20th February 2018) - Ozdemir, Serap Basoglu; Demirbas, Neslihan; Demirbas, Ahmet; Colak, Nesrin; Ayaz, Faik Ahmet
Abstract: The synthesis of new conazole analogues (8 a‐d ) was performed by three steps sequential reactions of compounds5 a, b containing the condensation with 4‐chlorophenylethanone, reduction of carbonyl function and O‐alkylation intermediates 2‐[(4‐Benzyl‐5‐[4‐(4‐fluorophenyl)piperazin‐1‐yl]methyl‐4 H ‐1, 2, 4‐triazol‐3‐yl)thio]‐1‐(4‐chlorophenyl)ethanol(7 a) and 2‐[(5‐[4‐(4‐fluorophenyl)piperazin‐1‐yl]methyl‐4‐phenyl‐4 H ‐1, 2, 4‐triazol‐3‐yl)thio]‐1‐phenylethanol(7 b) . The treatment of triazoles 4‐Benzyl‐5‐[4‐(4‐fluorophenyl)piperazin‐1‐yl]methyl‐2, 4‐dihydro‐4 H ‐1, 2, 4‐triazole‐3‐thiol (5 a ) and 5‐[4‐(4‐Fluorophenyl)piperazin‐1‐yl]methyl‐4‐phenyl‐4 H ‐1, 2, 4‐triazole‐3‐thiol (5 b ) with several amines in the presence of formaldehyde generated the corresponding Mannich bases (9‐12 ). All the reactions were examined under traditional and microwave irradiation conditions, and optimum conditions were defined. The antimicrobial, antiurease and antioxidant activities of the newly synthesized compounds were screened. Most of them had potent activity against to test microorganism. Especially mannich bases showed minimum inhibitory concentration (MIC) values between 0.24 and 1.9 μg/mL. Abstract : New hybrid molecules consisting of fluoroquinolone, fluorophenyl piperazine and azole moieties. Synthesized by microwave and conventional methods. The newly synthesized compounds wew screened for their antimicrobial, antiurease and antioxidant activities.